Solvent dependent morphological modification of micro-nano assembled Mn2O3/NiO composites for high performance supercapacitor applications. Issue 4 (March 2019) - Karuppaiah, M.; Sakthivel, P.; Asaithambi, S.; Murugan, R.; babu, G. Anandha; Yuvakkumar, R.; Ravi, G.
Abstract: The different attractive morphologies of micro-nano assembled sphere, pseudo sphere, rock candy and cube-like Mn2 O3 /NiO composites were synthesised by the facile solvothermal method through varying the solvents and their volume ratio. The structural, morphological and compositional properties of synthesised samples were investigated by using powder X-ray diffraction (XRD), FE-SEM, EDS and XPS. The TG/DTA results confirmed the transformation of MnCO3 /NiCO3 to Mn2 O3 /NiO structures. XRD results revealed that the synthesised samples exhibited the body-centred cubic of Mn2 O3 and face-centred cubic of NiO. FESEM images depicted the formation of different micro-nano assembled morphologies. XPS study confirmed the presence of manganese, nickel and oxygen elements and their oxidation states. Pseudocapacitance properties of Mn2 O3 /NiO electrodes were evaluated by cyclic voltammetry, galvanostatic charge-discharge and electrochemical impedance spectroscopy using 1M KOH electrolyte solution. The specific capacitance values of all the synthesised samples were calculated and the morphology of rock candy like Mn2 O3 /NiO composite exhibited superior properties of high specific capacitance of 566.21 Fg −1 at a current density of 0.5 Ag −1, better rate capability of 63.25% and good cycling stability of 87.42% capacitance retention even after 1000 cycles. From these results, the well morphological ordered Mn2 O3 /NiO composites may be preferred as the future electrode materials for electrochemical supercapacitor energy storage devices.